Umbilical cord prostaglandins in term and preterm parturition. (16th February 2016) - Hong, Joon-Seok; Romero, Roberto; Lee, Deug-Chan; Than, Nandor Gabor; Yeo, Lami; Chaemsaithong, Piya; Ahn, Soyeon; Kim, Jung-Sun; Kim, Chong Jai; Kim, Yeon Mee
Abstract: Objective : Prostaglandins (PGs) are considered the universal mediators of parturition. Amniotic fluid PGE2 and PGF2α concentrations increase before the onset of spontaneous labor at term, as well as during labor. This study was conducted to determine if the concentrations of umbilical cord PGE2 and PGF2 α change with advancing gestational age, spontaneous labor at term, and preterm labor (with and without funisitis). Methods : Umbilical cord (UC) tissue samples were obtained from women ( N = 158) with singleton pregnancies in the following groups: (1) term deliveries without labor (TNL; n = 20); (2) term deliveries with labor (TIL; n = 20); (3) spontaneous preterm deliveries (sPTD) with ( n = 20) and without acute funisitis ( n = 20); and (4) preeclampsia without labor ( n = 78). The concentrations of PGs were determined in different locations of the UC. PGE2 and PGF2α were measured by specific immunoassays. Non-parametric statistics were used for analysis. Results : (1) In spontaneous preterm deliveries, the median UC PGE2 concentration was higher in cases with funisitis than in those without funisitis (233.7 pg/µg versus 87.4 pg/µg of total protein, p = 0.001); (2) the median UC PGE2 concentration in sPTD with funisitis was also higher than that obtained from samples who had undergone labor at term (233.7 pg/µg versus 116.1 pg/µg of total protein, p = 0.03); (3) the UC PGE2 and PGF2α concentration increased as a function of advancing gestational age before 36 weeks (PGE2 : ρ = 0.59, p < 0.001; PGF2α : ρ = 0.39, p = 0.01), but not after 36 weeks (PGE2 : ρ = −0.1, p = 0.5; PGF2α : ρ = −0.2, p = 0.2); (4) the median UC concentrations of PGE2 and PGF2α at term was similar in samples obtained from women with and without labor (PGE2 : TNL 133.7 pg/µg versus TIL 116.1 pg/µg of total protein, p = 0.9; PGF2α : TNL 8.4 pg/µg versus TIL 8.1 pg/µg of total protein, p = 0.7); and (5) there was no correlation between UC PG concentration and gestational age at term pregnancy (PGE2 : ρ = 0.01, p = 0.9; PGF2α : ρ = 0.07, p = 0.7). Conclusions : (1) PGE2 concentrations in the UC are higher in the presence of acute funisitis than in the absence of this lesion; (2) spontaneous labor at term was not associated with a change in the UC concentration of PGE2 and PGF2α ; and (3) the UC concentrations of PGE2 and PGF2α increased as a function of gestational age. We propose that UC PGs act as inflammatory mediators generated in the context of fetal systemic inflammation.